1. Importance of Physical Exercise in Living Arrangements Artist - Leşe Ana-Cristina (Sciendo, 2016)
Increased occurrence of spine deviation is the result not only of modern technology hazards (for example, sitting in front of the computer for long hours) or lack of physical exercise, but also of specific posture related to the study of a musical instrument. The aim of this paper is the timely warning of children who choose to study a musical instrument about the spine deviations that can occur in time, also to refer them to a specialist and to encourage them to take up exercises meant to tone specific muscle groups. The study was conducted on two groups of students from the department of Musical interpretations, 1st and 2nd year, and two groups of students from the department of Painting and Photography and video, 1st year, at the "George Enescu" Arts University of Iaşi. The school screening method was used with the help of four MA students at the department of Kinetotherapy. The data were tabulated. We recommended that subjects be referred to specialised examinaton by doctors at the Pediatric Orthopedics clinic and have special sets of physical exercises.